A DOCÊNCIA EM MATEMÁTICA NA EDUCAÇÃO PROFISSIONAL INTEGRADA AO ENSINO MÉDIO - REIS, Luzia da Conceição Azevedo (2020)
This Master’s Thesis is part of the Research Group “School, Curriculum and Teacher Training”, of the Graduate Program in Education at the Federal University of Maranhao. It addresses teaching in mathematics in high school integrated with professional education, particularly in the Technical Courses of Administration and Environment of the College of Application in São Luis-Ma, in the period between 2017 to 2019. Its general objective is to analyze teaching in mathematics in Technical Courses of Administration and Environment in the context of the school. As specific objectives, it intends to characterize teaching in mathematics in technical courses, understanding the fundamentals of vocational education integrated with high school, identifying the theoretical methodological concepts that guide teaching in mathematics and to apprehending elements that contribute or hinder the exercise of teaching in mathematics in courses has studied. It is a qualitative research by, according to Bogdan and Biklen (1994), enabling to the subjects to present their personal perspective, exploring the meanings acquired by the investigation in which the investigated questions are not established through the operationalization of variables, being also formulated with the objective of investigating the phenomena in all their complexity and in a natural context, sustained in (LÜDKE and ANDRÉ, 1996), involving: bibliographical, documentary and field research carried out, through a case study (FREITAS, 2013; YIN, 2001). We used the semi-structured interview (TRIVIÑOS, 1987) as a technique and instrument for data collection with teachers, who taught mathematical discipline in technical courses, questionnaires to teachers and students, from the three years of high school (first, second and third) of the courses investigated totaling thirty tree research participants, being three teachers and thirty students. Teachers are professionals licensed in mathematics with qualification in postgraduate courses (master and doctorate) in different areas of knowledge. The theoretical foundation that led us in this research was based, regarding knowledge for teaching, in Freire, (1987); Shulman, (2005a, 2005b); Tardif (2002), to mathematical education Fiorentini, (1995); teaching in professional education in Machado, (2008), Oliveira (2010, 2013); Kuenzer, (2010), among others. The results point to the teaching practice in scientific mathematics of the common core, according to the Curricular Matrix of the course, as well as the technical core, Financial Mathematics and Statistics, developed, sometimes, in an expository class in the classroom, in Mathematics and Computer Labs and in moments of interdisciplinarity with interactive classes, in an inverted classroom based on elaborated projects and activities of Mathematical Modeling (ALMEIDA; SILVA; VERTUAN, 2013, p. 17). The experiences, with the inclusion of research projects, in multidisciplinary interaction with interactive methodologies of collective participation in debates, produced significant learning results. The class consisted of an interaction in content, practice and didactic pedagogical practices, drawing paths and possibilities for teaching. It was found that they were based on different references (FREIRE, 1979; DANTE, 2015; COSTA, 2008 OLIVEIRA, 2008). It was found out that they were based on different references (FREIRE, 1979; DANTE, 2015; COSTA, 2008 OLIVEIRA, 2008). The results also showed that the specificity of High School Integrated to professional education leads to a specific practical doc, which demands specific knowledge related to mathematics, from the researcher, from the experiential and from the contextual and attitudinal critical knowledge.